Association of National Institute Health Stroke Scale (NIHSS) Score on Admission with the Outcome of Acute Ischemic Stroke at Discharge from Hospital - Hasan, TM Hasibul; Habib, Khan Redzwan; Nuzhat, Elham; Gomes, Lilian Catherene; Hossain, Mohammad Murad; Miah, Md Titu; Azad, Khan Abul Kalam; Alam, Md Billal (Journal of Medicine, 2018)
Objectives: To determines the association of National Institute of Health Stroke Scale (NIHSS) score on admission with outcome of acute ischemic stroke during discharge from hospital. Materials & Methods: This hospital based observational study was done in medicine department of Dhaka Medical College Hospital involving 50 patients diagnosed as ischemic stroke on admission. The diagnosis of stroke was established by the clinical presentation, neuroimaging (CT scan/ MRI). They were thoroughly examined and assessed with NIHSS score at admission. All data were be collected by using a preformed data sheet and results were presented in standard method after statistical analysis. Results: Most of the patients were elder than 60 years of age and mean age of the patients was 60.34(±16.1) years at onset with a range of 24 to 76 years. Male were 116 (58%) and female were 84 (42%). Male to female ratio was1.4:1. Majority had hypertension (75.8%) followed by physical inactivity (67%), Diabetes (37.4%), smoking (33%), obesity (23.1%), family H/O stroke (20.9%) and dyslipideamia (15.4%). Higher NIHS score was associated with poor outcome (p value <0.05). Conclusion: Among the common risk factors, smoking, hypertension, diabetes and atrial fibrillation are associated with worse outcome at discharge. Similarly, higher NIHSS score at admission and high CCI is also associated with poor outcome. J MEDICINE JUL 2018; 19 (2) : 91-94